Effects of Apple Form on Energy Intake During a Mid-Afternoon Snack: A Preload Paradigm Study in School-Aged Children - Schwartz, Camille; Person, Ophélie; Szleper, Emilie; Nicklaus, Sophie; Tournier, Carole (Frontiers in Nutrition, 2021)
Consuming foods with a form or a texture that requires longer oral processing is a way to decrease food intake. Although this approach is promising for leveraging healthier eating patterns in adults, it has never been explored in children. This study evaluated whether starting a mid-afternoon snack by eating either apple segments or applesauce would modify hunger and subsequent food intake during this meal. Forty-four children (8-10 years old) participated in two videotaped mid-afternoon snacks during which they received one of the two forms of apple as a food preload followed 10 min later by ad libitum consumption of sweetened cottage cheese. They self-reported their level of hunger throughout consumption, and the weight of cottage cheese consumed was determined at the end of the snack. Children’s chewing capabilities and eating traits were parent-reported. Eating a raw apple increased oral exposure time and decreased bite size compared to eating applesauce. However, neither the reported hunger nor consecutive food intake were modified. Regardless of the meal, children eating fast had a higher ad libitum energy intake. The individual eating rate for the cottage cheese was correlated with the eating rate observed for applesauce but not for apple segments, the latter being associated with children’s chewing difficulties. This study suggests that the form of a fruit offered at the start of a mid-afternoon snack does not impact food intake; the findings clearly call for more exploration of satiation mechanisms related to food texture properties among children and indicate the need to consider children’s oral processing skills.